Experimental Effects of a Call-Center Disclaimer Regarding Confidentiality on Callers' Willingness to Make Disclosures Related to Terrorism. Issue 6 (2nd November 2019) - Williams, Michael J.; Bélanger, Jocelyn J.; Horgan, John; Evans, William P.
ABSTRACT: Utilizing a sample drawn to represent the general U.S. population, the present study experimentally tested whether a call-center's disclaimer regarding limits to caller confidentiality (i.e., that operators would be required to refer calls to law enforcement if callers were to discuss anyone who was a danger to themselves or others) affected disclosures related to a third party's involvement with terrorist groups, gangs, or such party's commission of assault and/or non-violent crimes. Disclaimer type did not significantly affect the number of terrorism-related disclosures. Furthermore, it did not significantly affect either the number of gang-related disclosures or reports of assault. However, the law enforcement referral disclaimer/condition reduced the number of disclosures of non-violent crimes that were not directly related to terrorism, gangs, or assault, though its effect accounted for less than one percent of the variance between conditions. Additionally, disclaimer type did not significantly affect willingness to recommend the call-center, nor did that effect vary significantly by age or sex. Implications for the call-center's role in addressing ideologically motivated violence (terrorism, violent extremism), as a form of secondary/targeted prevention, are discussed.